2000
DOI: 10.1002/1521-3757(20001215)112:24<4584::aid-ange4584>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Neue Anwendungen für polyfunktionalisierte Organometallverbindungen in der organischen Synthese

Abstract: In der zweiten Hälfte dieses Jahrhunderts wurde viel Forschungsarbeit in die Herstellung polarer Organometallreagentien investiert. Die hohe Reaktivität dieser Reagentien schloss die Gegenwart funktioneller Gruppen aus, und gute Chemo‐ und Stereoselektivitäten waren oft nur durch Transmetallierung zu erreichen. Die Synthese immer komplexerer Zielverbindungen und der Wunsch, ohne umständliche Schutzgruppenstrategien auszukommen, führten dazu, funktionalisierte Organometallreagentien in Retroynthesen zu verwende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 103 publications
(12 citation statements)
references
References 229 publications
0
10
0
2
Order By: Relevance
“…With the use of different probe molecules, the reactivity of the zinc methyl species on Zn/H-ZSM-5 catalyst was, therefore, investigated by solid-state 13 C MAS NMR spectroscopy. Typical results are summarized in Scheme 1, which indicates that the chemical nature of the zinc methyl species on the Zn/H-ZSM-5 catalyst is similar to that of organozinc compounds [48][49][50] in organometallic chemistry.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…With the use of different probe molecules, the reactivity of the zinc methyl species on Zn/H-ZSM-5 catalyst was, therefore, investigated by solid-state 13 C MAS NMR spectroscopy. Typical results are summarized in Scheme 1, which indicates that the chemical nature of the zinc methyl species on the Zn/H-ZSM-5 catalyst is similar to that of organozinc compounds [48][49][50] in organometallic chemistry.…”
Section: Resultsmentioning
confidence: 89%
“…We propose that the high reactivity of the zinc methyl species in the presence of proton donors on zeolite Zn/H-ZSM-5 (Scheme 1 a-d) can be understood on the basis of the similar chemistry of organozinc compounds. [48][49][50] For example, Coates [51] et al showed that organometallic reagents are readily converted into hydrocarbons in the presence of water. Bruce [52] et al, Noltes and Boersma, [53] and Coates and Ridley [54] demonstrated that organozinc compounds can be transformed into organozinc alkoxide RZnOR' and hydrocarbons by alcoholysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations